AP4S1 Splice-Site Mutation in a Case of Spastic Paraplegia Type 52 with Polymicrogyria - Carmona, S (2018)
Hereditary spastic paraplegias (HSPs) are a group of rare inherited neurodegenerative disorders that result from primary retrograde dysfunction of the long descending fibers of the corticospinal tract, causing lower limb spasticity and muscular weakness. This group of diseases has a heterogeneous clinical presentation. An extensive list of associated genes, different inheritance patterns, and ages at onset have been reported in HSPs.1 Spastic paraplegia type 52 (SPG52) is an autosomal recessive disease caused by AP4S mutations. The disease is characterized by neonatal hypotonia that progresses to hypertonia and spasticity in early childhood, developmental delay, mental retardation, and poor or absent speech. Febrile or afebrile seizures may also occur.